2017
DOI: 10.1021/acssuschemeng.7b01511
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Route for Molecularly Thin Cellulose Nanoribbons and Derived Nitrogen-Doped Carbon Electrocatalysts

Abstract: Ultrathin cellulose nanoribbons were extracted from earth-abundant biomass using 2,2,6,6-tetramethylpiperidine-1-oxyl-catalyzed (TEMPO-catalyzed) oxidation and sonication processes. By two TEMPO-oxide systems with different processing times, TEM and AFM observations indicate the obtained cellulose nanoribbons (Cel-NRs) with dimensions of 400–800 nm in length, 1.72–2.54 nm in width, and 0.78–2.67 nm in thickness. The dimension data indicate that the Cel-NRs from the TEMPO/NaBr/NaClO system are much shorter but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…also found that the mean thickness of cellulose nanofibrils extracted by using TEMPO/NaClO 2 /NaClO oxidation systems was around 0.8 nm, which is related to few layers cellulose molecular sheet. [ 7 ] More recently, Zhang et al. reported that the basic building block of the natural silkworm silk was 0.4 nm thick nanoribbons consisting of single β‐sheet layer and amorphous silk chains.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…also found that the mean thickness of cellulose nanofibrils extracted by using TEMPO/NaClO 2 /NaClO oxidation systems was around 0.8 nm, which is related to few layers cellulose molecular sheet. [ 7 ] More recently, Zhang et al. reported that the basic building block of the natural silkworm silk was 0.4 nm thick nanoribbons consisting of single β‐sheet layer and amorphous silk chains.…”
Section: Figurementioning
confidence: 99%
“…On the other hand, ChNFs prepared with elevated swelling time exhibits similar surface zeta potential while gradually growing carboxylate content from 1.34 to 1.78 mmol g −1 , also indicating that more hydroxyl groups along the inner (010) planar are esterified by MAH (Figure S15, Supporting Information). [ 7 ] After dispersing esterified β‐chitin in NaOH aqueous solution (pH = 11), nanofibrils with few molecular layers thick is exfoliated from elementary nanofibrils, as driven by the strong electrostatic repulsion between molecular sheets (Stage II). Longer incubation time in the pseudosolvent of DMSO/KOH tends to widen more (010) planar and thereby a decrease of nanofibrils thickness (Figure 3C; and Figure S16, Supporting Information).…”
Section: Figurementioning
confidence: 99%
“…The application of cellulose-based energy storage materials for lithium-ion batteries and supercapacitors has received unprecedented attention in recent years. [1][2][3][4][5] In particular, the use of nanocellulose as a carrier or a shaped material in combination with an electrochemically active material (e.g., a conductive polymer or carbon nanomaterial) to form energy storage materials, [6][7][8][9] and the direct carbonisation of nanocellulose into activated carbon materials [10][11][12][13][14] have been examined in detail. This increased attention regarding nanocellulose is closely related to its excellent properties, which are derived from its biomass source, i.e., wood.…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al controllably synthesized a series of 3D porous CNF aerogel with different dimeters using earth-abundant bamboo as precursors [12]. With the fast exploration of ocean, the abundant algae resources, mainly including browm, red, and green algas, have been extensively concerned [16][17][18][19][20][21][22][23][24][25]. Similar to bamboo, some of abundant seaweed (~ 30,000,000 tons per year) contain high cellulose, making them possible to produce CNF aerogel via a sustainable route.…”
Section: Manuscript a C mentioning
confidence: 99%